Phytochemical contents, antioxidant and antibacterial activity of the ethanolic extracts of Centella asiatica(L.) Urb.leaf and stem (Jahangirnagar University Journal of Biological Sciences, 2017)
Abstract not availableJahangirnagar University J. Biol. Sci. 6(1): 51-57, 2017 (June)